Intelligent Lighting System and Garbage Monitoring System - M.Prakash, U; Madan, Priyanshu; R. GokulAnand, K; Prabhakaran, S (International Journal of Engineering and Technology, 2018)
This paper aims at designing a system that focusses on two major societal issues in India i.e. improper garbage management and loss of energy from existing street lighting systems. We designed an intelligent lighting system Using embedded systems and machine learning algorithm we predict the environmental lighting conditions and accordingly change the behavior of the street lights. The present street lighting systems use timer or manual interaction to turn on and off the lights. But these methods are not energy efficient. In our model, we used Light Dependent Resistor LDR and algorithm to eliminate those drawbacks. In Garbage monitoring system, alerting the concerned authorities about the level of garbage collected was the most important aspect. In this system, an Ultrasonic sensor along with machine learning algorithm was used to solve the above situation.Â